η 3 ‐Coordination and Functionalization of the 2‐Phosphaethynthiolate Anion at Lanthanum(III)** - Watt, Fabian A.; Burkhardt, Lukas; Schoch, Roland; Mitzinger, Stefan; Bauer, Matthias; Weigend, Florian; Goicoechea, Jose M.; Tambornino, Frank; Hohloch, Stephan (Angewandte Chemie International Edition)
We present the η3-coordination of the 2-phosphaethynthiolate anion in the complex (PN)2La(SCP) (2) [PN=N-(2-(diisopropylphosphanyl)-4-methylphenyl)-2,4,6-trimethylanilide)]. Structural comparison with dinuclear thiocyanate-bridged (PN)2La(μ-1,3-SCN)2La(PN)2 (3) and azide-bridged (PN)2La(μ-1,3-N3)2La(PN)2 (4) complexes indicates that the [SCP]− coordination mode is mainly governed by electronic, rather than steric factors. Quantum mechanical investigations reveal large contributions of the antibonding π*-orbital of the [SCP]− ligand to the LUMO of complex 2, rendering it the ideal precursor for the first functionalization of the [SCP]− anion. Complex 2 was therefore reacted with CAACs which induced a selective rearrangement of the [SCP]− ligand to form the first CAAC stabilized group 15–group 16 fulminate-type complexes (PN)2La{SPC(RCAAC)} (5 a,b, R=Ad, Me). A detailed reaction mechanism for the SCP-to-SPC isomerization is proposed based on DFT calculations.
Keywords: General Chemistry; Catalysis

Electronic Structure of a Diiron Complex: A Multitechnique Experimental Study of [(dppf)Fe(CO) 3]+/0 - Winkler, Mario; Schnierle, Marc; Ehrlich, Felix; Mehnert, Kim-Isabelle; Hunger, David; Sheveleva, Alena M.; Burkhardt, Lukas; Bauer, Matthias; Tuna, Floriana; Ringenberg, Mark R.; van Slageren, Joris (Inorganic Chemistry)
Here we explore the electronic structure of the diiron complex [(dppf)Fe(CO)3]0/+ [10/+; dppf = 1,1′-bis(diphenylphosphino)ferrocene] in two oxidation states by an advanced multitechnique experimental approach. A combination of magnetic circular dichroism, X-ray absorption and emission, high-frequency electron paramagnetic resonance (EPR), and Mössbauer spectroscopies is used to establish that oxidation of 10 occurs on the carbonyl iron ion, resulting in a low-spin iron(I) ion. It is shown that an unequivocal result is obtained by combining several methods. Compound 1+ displays slow spin dynamics, which is used here to study its geometric structure by means of pulsed EPR methods. Surprisingly, these data show an association of the tetrakis[3,5-bis(trifluoromethylphenyl)]borate counterion with 1+.
Keywords: Inorganic Chemistry; Physical and Theoretical Chemistry

Planar Iron Hydride Nanoclusters: Combined Spectroscopic and Theoretical Insights into Structures and Building Principles - Chakraborty, Uttam; Bügel, Patrick; Fritsch, Lorena; Weigend, Florian; Bauer, Matthias; Jacobi von Wangelin, Axel (ChemistryOpen)
The controlled assembly of well-defined planar nanoclusters from molecular precursors is synthetically challenging and often plagued by the predominant formation of 3D-structures and nanoparticles. Herein, we report planar iron hydride nanoclusters from reactions of main group element hydrides with iron(II) bis(hexamethyldisilazide). The structures and properties of isolated Fe4, Fe6, and Fe7 nanoplatelets and calculated intermediates enable an unprecedented insight into the underlying building principle and growth mechanism of iron clusters, metal monolayers, and nanoparticles.
Keywords: General Chemistry

In Krisen erzählen – von Krisen erzählen. Sprachliche, literarische und mediale Dimensionen.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Networks - Sackel, Johanna; Wöbse, Anna-Katharina (A Cultural History of the Sea in the Global Age)

Mehrdeutigkeiten
Keywords: General Earth and Planetary Sciences; General Environmental Science

Register and Instruction Coverage Analysis for Different RISC-V ISA Modules - Adelt, Peer; Koppelmann, Bastian; Müller, Wolfgang; Scheytt, Christoph (Workshop Methoden und Beschreibungssprachen zur Modellierung und Verifikation von Schaltungen und Systemen (MBMV 2021))

Loyalty programs as travel companions: Complementary service features across customer journey stages - Steinhoff, Lena; Zondag, Marcellis M. (Journal of Business Research)
Keywords: Marketing

 Zeitschrift für Romanische Sprachen und ihre Didaktik

Konstruktionen und Konstruktionslernen

 Zeitschrift für Romanische Sprachen und ihre Didaktik

Phase Noise Investigation for a Radar System with Optical Clock Distribution - Kruse, Stephan; Bahmanian, Meysam; Kneuper, Pascal; Kress, Christian; Kurz, Heiko G.; Schneider, Thomas; Scheytt, Christoph (The 17th European Radar Conference)

Determination of Crystal-Field Splitting Induced by Thermal Oxidation of Titanium - Wojtaszek, Klaudia; Błachucki, Wojciech; Tyrała, Krzysztof; Nowakowski, Michał; Zaja̧c, Marcin; Stȩpień, Joanna; Jagodziński, Paweł; Banaś, Dariusz; Stańczyk, Wiktoria; Czapla-Masztafiak, Joanna; Kwiatek, Wojciech M.; Szlachetko, Jakub; et al. (The Journal of Physical Chemistry A)
Keywords: Physical and Theoretical Chemistry

Comparing the Effects of a Different Social Partner (Social Robot vs. Human) on Children's Social Referencing in Interaction - Tolksdorf, Nils F.; Crawshaw, Camilla E.; Rohlfing, Katharina (Frontiers in Education)
Social robots have emerged as a new digital technology that is increasingly being implemented in the educational landscape. While social robots could be deployed to assist young children with their learning in a variety of different ways, the typical approach in educational practices is to supplement the learning process rather than to replace the human caregiver, e.g., the teacher, parent, educator or therapist. When functioning in the role of an educational assistant, social robots will likely constitute a part of a triadic interaction with the child and the human caregiver. Surprisingly, there is little research that systematically investigates the role of the caregiver by examining the ways in which children involve or check in with them during their interaction with another partner — a phenomenon that is known as social referencing. In the present study, we investigated social referencing in the context of a dyadic child–robot interaction. Over the course of four sessions within our longitudinal language-learning study, we observed how 20 pre-school children aged 4–5 years checked in with their accompanying caregivers who were not actively involved in the language-learning procedure. The children participating in the study were randomly assigned to either an interaction with a social robot or a human partner. Our results revealed that all children across both conditions utilized social referencing behaviors to address their caregiver. However, we found that the children who interacted with the social robot did so significantly more frequently in each of the four sessions than those who interacted with the human partner. Further analyses showed that no significant change in their behavior over the course of the sessions could be observed. Findings are discussed with regard to the caregiver's role during children's interactions with social robots and the implications for future interaction design.
Keywords: Education

Progressive Reduction of Iconic Gestures Contributes to School-Aged Children’s Increased Word Production - Rohlfing, Katharina; Mertens, Ulrich (Frontiers in Psychology)

Do Shy Preschoolers Interact Differently When Learning Language With a Social Robot? An Analysis of Interactional Behavior and Word Learning - Tolksdorf, Nils Frederik; Viertel, Franziska E.; Rohlfing, Katharina J. (Frontiers in Robotics and AI)
Temperamental traits can decisively influence how children enter into social interaction with their environment. Yet, in the field of child–robot interaction, little is known about how individual differences such as shyness impact on how children interact with social robots in educational settings. The present study systematically assessed the temperament of 28 preschool children aged 4–5 years in order to investigate the role of shyness within a dyadic child–robot interaction. Over the course of four consecutive sessions, we observed how shy compared to nonshy children interacted with a social robot during a word-learning educational setting and how shyness influenced children’s learning outcomes. Overall, results suggested that shy children not only interacted differently with a robot compared to nonshy children, but also changed their behavior over the course of the sessions. Critically, shy children interacted less expressively with the robot in general. With regard to children’s language learning outcomes, shy children scored lower on an initial posttest, but were able to close this gap on a later test, resulting in all children retrieving the learned words on a similar level. When intertest learning gain was considered, regression analyses even confirmed a positive predictive role of shyness on language learning gains. Findings are discussed with regard to the role of shyness in educational settings with social robots and the implications for future interaction design.

Wurzel - Heidgen, Michael (Metzler Lexikon literarischer Symbole)

This is my Fight Song - Uppenkamp, Vera; Neumann, Anna; Kammeyer, Katharina (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

"Wenn sich die Mitte auflöst...", ist das kein Verlust für die Religionspädagogik - ein bilanzierender Tagungsrückblick mit Augenzwinkern - Uppenkamp, Vera; Höger, Christian (Theo-Web. Zeitschrift für Religionspädagogik)

Art. Mädchen/Frauen - Uppenkamp, Vera (Das wissenschaftlich-religionspädagogische Lexikon im Internet www.wirelex.de)

"Gib mir was zu trinken, ich habe Durst..." Laientheologie nach Harald Schroeter-Wittke bei den Toten Hosen - Pinsch, Jan Christian (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Rezension zu Oliver Arnold, „Entjudung“ von Theologie und Kirche. Das Eisenacher „Institut zur Erforschung und Beseitigung des jüdischen Einflusses“ auf das deutsche kirchliche Leben 1939-1945, Bd. 6 Christentum und Zeitgeschichte, Leipzig 2020 - Pinsch, Jan Christian; Lerke, Stephanie (Paderborner Historische Mitteilungen)

Viel Lärm um die Stille. Die Geschichte des Raums der Stille an der Universität Paderborn im Spannungsfeld zwischen Religionsfreiheit und weltanschaulicher Neutralität - Pinsch, Jan Christian (Paderborner Historische Mitteilungen)

'Keine Gefangenen' oder 'Hyper Hyper' - Kommunikationen, Medien und Kulturen als Motoren gesellschaftlicher Transformationen. - Jacke, Christoph (Medienkultur als kritische Gesellschaftsanalyse. Festschrift für Rainer Winter.)

‚Deutsche’ Pop-Rezeption – zwischen journalistischen Trivialitäten und nationalen Eigenarten? - Jacke, Christoph (Gehört „deutsche“ Popmusik ins Museum? Materialien zu und von der Fünften Pop-Dekadentagung)

Ethische Bildung und inklusionsorientierter Religionsunterricht - Kammeyer, Katharina (Handbuch ethische Bildung. Religionspädagogische Fokussierungen)

This is my Fight Song - Kammeyer, Katharina; Neumann, Anna; Uppenkamp, Vera (Musik als Lebensmittel. Kulturwissenschaftlich-theologische Rationen für ein Jahr)

Improved non-linear devices for quantum applications - Gil López, Jano; Santandrea, Matteo; Roland, Ganaël; Brecht, Benjamin; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Silberhorn, Christine (New Journal of Physics)

Universal compressive tomography in the time-frequency domain - Gil López, Jano; Teo, Yong Siah; De, Syamsundar; Brecht, Benjamin; Jeong, Hyunseok; Silberhorn, Christine; Sánchez-Soto, Luis L. (Optica)

Musik und Sprache in Schauspielmusiken des 19. Jahrhunderts - Tumat, Antje

Learning to play golf for elderly people with subjective memory complaints: feasibility of a single‐blinded randomized pilot trial - Stroehlein, Julia K.; Vieluf, Solveig; Zimmer, Philipp; Schenk, Alexander; Oberste, Max; Gölz, Christian Johannes; van den Bongard, Franziska; Reinsberger, Claus (BMC Neurology)
Abstract Background Subjective Memory Complaints (SMC) in elderly people due to preclinical Alzheimer’s Disease may be associated with dysregulation of the Kynurenine Pathway (KP), with an increase in neurotoxic metabolites that affect cognition. Golf is a challenging sport with high demands on motor, sensory, and cognitive abilities, which might bear the potential to attenuate the pathological changes of preclinical AD. This trial investigated the feasibility of learning to play golf for elderly with cognitive problems and its effects on cognitive functions and the KP. Methods In a 22-week single-blinded randomized controlled trial, elderly people with SMC were allocated to the golf ( n = 25, 180 min training/week) or control group ( n = 21). Primary outcomes were feasibility (golf exam, adherence, adverse events) and general cognitive function (Alzheimer’s Disease Assessment Scale). Secondary outcomes include specific cognitive functions (Response Inhibition, Corsi Block Tapping Test, Trail Making Test), KP metabolites and physical performance (6-Minute-Walk-Test). Baseline-adjusted Analysis-of-Covariance was conducted for each outcome. Results 42 participants were analyzed. All participants that underwent the golf exam after the intervention passed it (20/23). Attendance rate of the golf intervention was 75 %. No adverse events or drop-outs related to the intervention occurred. A significant time*group interaction ( p = 0.012, F = 7.050, Cohen’s d = 0.89) was found for correct responses on the Response Inhibition task, but not for ADAS-Cog. Moreover, a significant time*group interaction for Quinolinic acid to Tryptophan ratios ( p = 0.022, F = 5.769, Cohen’s d = 0.84) in favor of the golf group was observed. An uncorrected negative correlation between attendance rate and delta Quinolinic acid to Kynurenic acid ratios in the golf group ( p = 0.039, r =-0.443) was found as well. Conclusions The findings indicate that learning golf is feasible and safe for elderly people with cognitive problems. Preliminary results suggest positive effects on attention and the KP. To explore the whole potential of golfing and its effect on cognitive decline, a larger cohort should be studied over a longer period with higher cardiovascular demands. Trial registration The trial was retrospectively registered (2nd July 2018) at the German Clinical Trials Register ( DRKS00014921 ).
Keywords: Clinical Neurology; General Medicine

Generalized tonic-clonic seizures are accompanied by changes of interrelations within the autonomic nervous system. - Vieluf, S; Hasija, Tanuj; Schreier, PJ; El Atrache, R; Hammond, S; Mohammadpour Touserkani, F; Sarkis, RA; Loddenkemper, T; Reinsberger, Claus (Epilepsy Behav)

Electrophysiological signatures of dedifferentiation differ between fit and less fit older adults - Gölz, Christian Johannes; Mora, Karin; Stroehlein, Julia Kristin; Haase, Franziska Katharina; Dellnitz, Michael; Reinsberger, Claus; Vieluf, Solveig (Cognitive Neurodynamics)
Abstract Cardiorespiratory fitness was found to influence age-related changes of resting state brain network organization. However, the influence on dedifferentiated involvement of wider and more unspecialized brain regions during task completion is barely understood. We analyzed EEG data recorded during rest and different tasks (sensory, motor, cognitive) with dynamic mode decomposition, which accounts for topological characteristics as well as temporal dynamics of brain networks. As a main feature the dominant spatio-temporal EEG pattern was extracted in multiple frequency bands per participant. To deduce a pattern’s stability, we calculated its proportion of total variance among all activation patterns over time for each task. By comparing fit (N = 15) and less fit older adults (N = 16) characterized by their performance on a 6-min walking test, we found signs of a lower task specificity of the obtained network features for the less fit compared to the fit group. This was indicated by fewer significant differences between tasks in the theta and high beta frequency band in the less fit group. Repeated measures ANOVA revealed that a significantly lower proportion of total variance can be explained by the main pattern in high beta frequency range for the less fit compared to the fit group [F(1,29) = 12.572, p = .001, partial η 2 = .300]. Our results indicate that the dedifferentiation in task-related brain activation is lower in fit compared to less fit older adults. Thus, our study supports the idea that cardiorespiratory fitness influences task-related brain network organization in different task domains.
Keywords: Cognitive Neuroscience

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Gölz, Christian Johannes; Mora, K.; Rudisch, J.; Gaidai, Roman; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

Thermostable water reservoirs in the interlayer space of a sodium hectorite clay through the intercalation of γ-aminopropyl(dimethyl)ethoxysilane in toluene - Keil, Waldemar; Zhao, Kai; Oswald, Arthur; Bremser, Wolfgang; Schmidt, Claudia; Hintze-Bruening, Horst (Physical Chemistry Chemical Physics)
Thermostable compartmentalized sodium-water sites through intercalated γ-aminopropyl-dimethyl-ethoxy silane in synthetic hectorite.
Keywords: Physical and Theoretical Chemistry; General Physics and Astronomy

Mechanism and equilibrium thermodynamics of H- and J-aggregate formation from pseudo isocyanine chloride in water - Hämisch, Benjamin; Huber, Klaus (Soft Matter)
Pseudo isocyanine chloride monomers equilibrate with H-oligomers and, separated by a threshold, with H-oligomers and fiber-like J-aggregates. The mechanism and thermodynamics of J-aggregate formation is interpreted with the concept of chain growth.
Keywords: Condensed Matter Physics; General Chemistry

Self-Assembled Fibrinogen Hydro- and Aerogels with Fibrin-like 3D Structures - Hense, Dominik; Büngeler, Anne; Kollmann, Fabian; Hanke, Marcel; Orive, Alejandro; Keller, Adrian; Grundmeier, Guido; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)
Keywords: Materials Chemistry; Polymers and Plastics; Biomaterials; Bioengineering

Multiresponsive Polymer Nanoparticles Based on Disulfide Bonds - Wagner, Maximilian; Krieger, Anja; Minameyer, Martin; Hämisch, Benjamin; Huber, Klaus; Drewello, Thomas; Gröhn, Franziska (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Thermodynamic Analysis of the Self‐Assembly of Pseudo Isocyanine Chloride in the Presence of Crowding Agents - Hämisch, Benjamin; Pollak, Roland; Ebbinghaus, Simon; Huber, Klaus (ChemSystemsChem)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Classification of visuomotor tasks based on electroencephalographic data depends on age-related differences in brain activity patterns - Goelz, C.; Mora, K.; Rudisch, J.; Gaidai, R.; Reuter, E.; Godde, B.; Reinsberger, Claus; Voelcker-Rehage, C.; Vieluf, S. (Neural Networks)
Keywords: Artificial Intelligence; Cognitive Neuroscience

Twenty-four-hour patterns in electrodermal activity recordings of patients with and without epileptic seizures. - Vieluf, S; Amengual-Gual, M; Zhang, B; El Atrache, R; Ufongene, C; Jackson, MC; Branch, S; Reinsberger, Claus; Loddenkemper, T (Epilepsia)

Exercise and sports after COVID-19-Guidance from a clinical perspective. - Halle, M; Bloch, W; Niess, AM; Predel, HG; Reinsberger, Claus; Scharhag, J; Steinacker, J; Wolfarth, B; Scherr, J; Niebauer, J (Transl Sports Med)

The effects of repetitive head impacts on postural control: A systematic review. - Bonke, EM; Southard, J; Buckley, TA; Reinsberger, Claus; Koerte, IK; Howell, DR (J Sci Med Sport)

Head injuries in professional football (soccer): Results of video analysis verified by an accident insurance registry. - Krutsch, V; Krutsch, W; Härtl, J; Bloch, H; Alt, V; Klein, C; Reinsberger, Claus; Seiffert, R; Huber, L; Weber, J (PLoS One)

Evaluation of Open-Source and Pre-Trained Deep Convolutional Neural Networks Suitable for Player Detection and Motion Analysis in Squash. - Brumann, C; Kukuk, M; Reinsberger, Claus (Sensors (Basel))

Zunftbankett und Göttermahl – Mahlzeiten im Leben und Werk niederländischer Maler im 16. Jahrhundert. Ansätze zur Interpretation - Harnack, Maria (Paderborner Historische Mitteilungen)

Afrikanische Masken und Skulpturen der Sammlung Karl-Josef Scheideler des Lippischen Landesmuseums Detmold - Duschner, Paul

Spuren des Kolonialismus in der Airport Art: Vier Beispiele aus Westfalen - Duschner, Paul (Koloniale Welten in Westfalen)

Entwicklung einer Methode zur differenzierten Messung des Wachstums der Rissenden von Innenrissen mit der Elektropotentialmethode - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta

Effektivität von Luftreinigern zur Reduzierung des COVID-19-Infektionsrisikos/ Efficacy of air purifiers in reducing the risk of COVID-19 infections - Schumacher, Stefan; Asbach, Christof; Schmid, Hans-Joachim (Gefahrstoffe)
Luftreiniger werden derzeit häufig als mögliches Hilfsmittel zur Minimierung des Infektionsrisikos im Rahmen der COVID-19-Pandemie diskutiert. Dabei taucht oft die Frage auf, ob Luftreiniger grundsätzlich in der Lage sind, Viren oder virenbeladene Tröpfchen abzuscheiden. Ziel dieses Artikels ist es, die wesentlichen Grundlagen der Wirkungsweise von Luftreinigern und Filtern zu beschreiben, Methoden zur Messung der Reinigungswirkung im Größenbereich von Viren und virenbeladenen Tröpfchen aufzuzeigen sowie typische Szenarien zum Betrieb von Luftreinigern in einem mathematischen Modell zu erfassen. Darauf basierend können die Möglichkeiten und Grenzen von Luftreinigern für reale Anwendungsfälle besser eingeschätzt werden.